Formalin Analysis of Food Ingredients in Palu - Rismawaty Sikanna; Ivone Venita Sarapun; Dwi Juli Puspitasari (Al-Kimia, 2018)
Research on formalin analysis of food ingredients in Palu has been conducted. The purpose of the research is to find out formalin content in some food. The analyzed samples were foods that marketed in Palu, such as salt fish, noodles, mujair fish, and tofu obtained from several places in Palu. The qualitative analysis of formalin done before measured of formalin quantitatively. The data on formalin found by UV-Vis spectrophotometer with the wavelength of 385 nm. Formalin content of salted fish, noodles, Mujair fish, and tofu were 2,005 ± 0,187ppm, 2,183 ±0,231ppm, 1,931 ±0,174 ppm, and 1,957 ±0,254 ppm, respectively.